Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Keinginan Berbelanja Pada Coco Mart Tabanan - Ni Wayan Ari Sudiartini; Ni Ketut Murdani; Ni Kadek Candra Dewi (Jurnal Ilmiah Satyagraha, 2019)
This research aims to find out how the influence of service quality and customer satisfaction to desire to shop at Coco Mart Tabanan. The data used in this research is quantitative data and then processed using multiple linear regression analysis. Population in this research were consumers who made purchases in Coco Mart Tabanan, with a sample of 60 people.Test results of multiple linear regression analysis obtained equation Y = - 0,465 + 0,236X1+ 0,289X2,  which means the quality of service variables (X1) and customer satisfaction (X2) have a significant positive effect on the desire to shop (Y). The correlation test results show that the correlation coefficient of = 0,889 lies between 0,80-1,00 which means that the effect between service quality  (X1) and customer satisfaction (X2) with shopping desire (Y) is very strong. Determination test results, adjusted amount of R2 is 0,790 this means the influence of service quality and customer satisfaction to the desire to shop for 79,0% while the remaining 21,0% influenced by other factors not examined. The results of the f test and t test show that the hypothesis which reads “ there is a significant influence between service quality (X1) and customer satisfaction (X2) on shopping desire (Y) “ can be received by testing significant level 0,000 is smaller than 0,05.